Morpho-physiological characteristics and interactions of isolates of Mycogone perniciosa (Magnus) Delacr - Glamočlija Jasmina M. (Zbornik Matice Srpske za Prirodne Nauke, 2007)
Mycogone perniciosa (Magnus) Delacr., which causes wet bubble disease of Agaricus bisporus Lange (Imb), results in a considerable crop loss on mushroom farms in Serbia. The isolation and identification of five isolates of M. perniciosa from diseased fruit bodies of white button mushroom from mushroom units in Serbia, Bosnia and Herzegovina and Holland were made. Morpho-physiological characteristics and inter-relationships of the obtained isolates were studied. Macroscopic and microscopic investigations of different zones between colonies of the isolates of M. perniciosa revealed the phenomenon of the hyphal interference between different isolates. The obtained results suggest that hyphal interference could serve as an additional parameter for a more reliable determination of fungal specifity.